2016
DOI: 10.1111/nmo.12926
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor monotherapy and the risk of cardiovascular events in patients with gastro‐esophageal reflux disease: a meta‐analysis

Abstract: PPI monotherapy can be a risk factor for cardiovascular adverse events. Omeprazole could significantly increase the risk of cardiovascular events and, so, should be used carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 48 publications
(106 reference statements)
4
25
1
1
Order By: Relevance
“…This is the most current meta‐analysis examining PPI monotherapy and cardiovascular risk and is, to our knowledge, the only study to compare the results of both observational and randomised studies. The findings from our pooled analysis of trial data differed from those of Sun et al, who found a 70% increased risk of major adverse cardiovascular events with PPI therapy in a meta‐analysis of 16 randomised controlled trials. However, Sun et al.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is the most current meta‐analysis examining PPI monotherapy and cardiovascular risk and is, to our knowledge, the only study to compare the results of both observational and randomised studies. The findings from our pooled analysis of trial data differed from those of Sun et al, who found a 70% increased risk of major adverse cardiovascular events with PPI therapy in a meta‐analysis of 16 randomised controlled trials. However, Sun et al.…”
Section: Discussioncontrasting
confidence: 99%
“…included different control groups, including histamine‐2‐receptor antagonists and surgery. Within this study, subgroup analysis demonstrated that histamine‐2‐receptor antagonists were strongly associated with a decreased risk of adverse cardiovascular outcomes as compared to PPI, with a reduction in risk with histamine‐2‐receptor antagonist therapy observed across all included studies . The aetiology of the cardioprotective effect of histamine‐2‐receptor antagonists as compared to PPI observed is unclear and may merit further study.…”
Section: Discussionmentioning
confidence: 76%
“…We also found that only long‐term use of PPIs was significantly associated with increased rates of the cardiovascular outcomes. A recent meta‐analysis of 16 prior randomized trials revealed that PPI monotherapy was associated with increased risk of cardiovascular events in patients with GERD and especially for long‐term users, which is in line with our findings . The large randomized COGENT (Clopidogrel and the Optimization of Gastrointestinal Events Trial) study did not find omeprazole to increase the risk of cardiovascular events in patients with prior cardiovascular disease .…”
Section: Discussionsupporting
confidence: 91%
“…We cannot exclude a power issue with H2RA in this population, as most individuals were treated with PPIs. Prior studies have reported conflicting results regarding H2RA and the risk of MI . H2RA was not associated with ischemic stroke which strengthens the confidence in this finding.…”
Section: Discussionsupporting
confidence: 75%
“…We read with great interest the timely meta-analysis of randomized clinical trials by Sun et al, who found a "70% increased cardiovascular risk" in patients using proton pump inhibitors (PPIs) as monotherapy for gastro-esophageal reflux disease. 1 In fact, overuse of PPIs has recently raised concern on their actual safety profile because of the unexpected occurrence of adverse events. 2 Their cardiovascular safety is debated, especially the risk of myocardial infarction in patients without prior history of cardiovascular diseases.…”
Section: Association Between the Use Of Proton Pump Inhibitors And Camentioning
confidence: 99%